Upper Ordovician carbon isotope chemostratigraphy and a high-resolution assessment of the Hirnantian Stage in the Baltic Sea subsurface - Gunnarsson, Niklas; Calner, Mikael; Rasmussen, Christian M. O.; Wu, Rongchang; Lehnert, Oliver; Dahlqvist, Peter (GFF, 2024)
Based on a new deep drilling on southern Gotland (Sweden), this study is the first to document the carbon isotope chemostratigraphy of the Upper Ordovician through lowermost Silurian sedimentary record from the central parts of the Baltic Sea subsurface. The lithological record of the Stora Sutarve core has similarities with adjacent successions in both the Viki core in the East Baltic area and the Borenshult core in the Swedish mainland. The core includes the Kahula (including 13 bentonites in the "Kinnekulle K-bentonite complex"), Hirmuse(?), R & auml;gavere, Paekna, Jonstorp, Loka, Motala and Kallholn formations. Several of the internationally recognized upper Ordovician delta C-13 excursions have been identified in the core, including the Guttenberg Isotope Carbon Excursion (GICE), Moe excursion, Hirnantian Isotope Carbon Excursion (HICE), and an undefined early Silurian carbon isotope excursion, presumably the Early Aeronian Carbon Isotope Excursion (EACIE). We particularly address the microstratigraphy of the Hirnantian Stage and the finer details of the HICE, which is not fully complete and entirely confined to the 2.09-m-thick Loka Formation. This formation yields abundant, but low-richness brachiopod faunas characteristic of the Hirnantian Stage and is, based on erosional-depositional surfaces and facies, interpreted as reflecting interglacial warming and eustatic transgression related to ice-sheet contraction in Gondwana. Based on very dense carbon isotope sampling we identify four clusters of delta C-13 values that aid to define significant changes in the preserved record of the HICE and which may facilitate global correlation of the succession and the herein interpreted sea-level record.